(untitled) (Revista Espacio Regional, 2020)
Health management and ruralities are already two subjects of a wide complexity, to make an approximation to them is the objective of this writing through an ethnographic exercise following the experience of the rural health team of Puerto Montt. This article presents some of the final considerations and reflections produced around the reading that the officials have about the implementation of the program "improvement of equity in rural health" during the first years of its gestation and initiation. Some of the conclusions suggest that the management models that underlie the modernization of the State continue to hegemonically and centrally think about health policies, that the lags between the political and the administrative remain where not only the ruralities are invisible but also the actors responsible for the implementation and tensions that arise in the practices of public work.